On estimates for the parameters of a Gaussian stationary process with the spectral density [P(iλ)]^{-2} - Pisarenko, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Ф. Писаренко. Об оценках параметров гауссовского стационарного процесса со спектральной плотностью [P(iλ)]^{-2}V. Pisarenko. Apie stacionaraus Gauso proceso su spektriniu tankiu [P(iλ)]^{-2} parametrų įvertinimus